Photodynamic Therapy in Orthodontics: A Literature Review - Marcin Olek; Agnieszka Machorowska-Pieniążek; Wojciech Stós; Janusz Kalukin; Dorota Bartusik-Aebisher; David Aebisher; Grzegorz Cieślar; Aleksandra Kawczyk-Krupka (Pharmaceutics, 2021)
Treatment of malocclusions using fixed orthodontic appliances makes it difficult for patients to perform hygiene procedures. Insufficient removal of bacterial biofilm can cause enamel demineralization, manifesting by visible white spot lesions or periodontal diseases, such as gingivitis periodontitis or gingival hyperplasia. The classic methods of preventing the above problems include, in addition to proper hygiene, ultrasonic scaling, periodontal debridement, and oral rinses based on chlorhexidine. New alternative methods of reducing plaque around brackets are being developed. There is a growing interest among researchers in the possibility of using photodynamic therapy in orthodontics. A literature search for articles corresponding to the topic of this review was performed using the PubMed and Scopus databases and the following keywords: ‘photodynamic therapy’, ‘orthodontics’, and ‘photosensitizer(s)’. Based on the literature review, two main directions of research can be distinguished: clinical research on the use of photodynamic therapy in the prevention of white spot lesions and periodontal diseases, and ex vivo research using a modified orthodontic adhesive by adding photosensitizers to them. Methylene blue is the most frequently used photosensitizer in clinical trials. The effectiveness of antimicrobial photodynamic therapy is mainly compared to the ultrasonic scaler as a single therapy or as an adjunct to the ultrasonic scaler. In their conclusions, the researchers most often emphasize the effectiveness of antimicrobial photodynamic therapy in reducing microbial levels in patients treated with fixed appliances and the possibility of using it as an alternative to routine procedures aimed at maintaining a healthy periodontium. The authors suggest further research on the use of photodynamic therapy to prove the validity of this method in orthodontics. It should also not be forgotten that proper hygiene is the basis for maintaining oral cavity health, and its neglect is a contraindication to orthodontic treatment.